Prebiotic Milk Shake and Its Health Benefits - Endang S Rahayu (Indonesian Food and Nutrition Progress, 2004)
Study on the effect of prebiotic consumption to the fecal material volunteer was conducted at Center for Food and Nutrition Studies, Gadjah Mada University. Aim of this study was to investigate to health benefical effect of prebiotic product directly using volunteers. Prebiotic product used in this study was StefitTM-non fat milk shake which contains dietary fiber, antioxidant (vitamin E and C), calcium, and chicory root extract (inulin) as prebiotic. Seven healthy volunteers (5 males and 2 females), 30-40 years old, were recruited for this study. During the study (6 weeks), volunteers were asked to avoid antimicrobial drugs and fermented foods containing life microbial cells. The volunteers were divided into two group, group 1 (consist of 2 persons) were asked to consumed original non-fat milk, while group 2 (5 persons) consumed non-fat milk shake prebiotics. Consumption of milk shake was done every day (2 sachets per day, morning and afternoon) during 4 weeks. Twice a week, fecal materials of volunteers were microbiologically analyzed, including a week before and after consumption. Diet of each volunteer was not controlled, they ate as their usual food every day and the menus were recorded. Consumption of milk shake prebiotic by normal healthy volunteer resulted in increased the number of fecal lactic acid producing bacteria (from about 106 to 107 CFU/g fecal material), and decreased the population of fecal enterobacteriaceae and coliform. According to the data, fecal lactic acid producing bacteria of volunteers who consumed the original milk shake were mostly constant. Conclusion of this study is the increasing number of lactic acid bacteria induced by prebiotic inulin in the colon has the potential to improve the health and well being of the host.